To Determine the Outcome of Exhumation in Pakistan - Rabail Altaf, Muhammad Rafiq Sheikh, Mansoor Ali, Pushpa, Muhammad Ayob Jogi, Pardeep Kumar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Exhumation, a delicate process involving the examination of deceased bodies, serves various purposes such as investigating homicides, suicides, and DNA analysis. Methods: This retrospective cohort study, conducted from January to July 2023 at Gambat Medical College, Pakistan, utilized a convenience sampling technique with a sample size of 377 determined by WHO guidelines. Data on exhumed cases were collected using structured forms and analyzed for demographic characteristics, condition of bodies, and causes of death. Results: The study included predominantly male individuals (72.1%) with a mean age of 39.36 years, primarily from urban areas (68.4%). Reasons for exhumation were homicide (69.2%), suicide (19.1%), and DNA analysis (11.7%). Males were more common in younger age groups and identifiable conditions, with varying causes of death including firearm injuries (22.0%) and blunt injuries (16.7%). Conclusion: Exhumation outcomes in Pakistan reveal demographic trends, varying causes of death, and success rates. Findings emphasize the need for culturally sensitive forensic practices and highlight regional disparities in methods of homicide. Further research incorporating broader contexts is essential for comprehensive understanding and informed interventions. Keywords: Exhumation, forensic investigation, homicide, Pakistan, demographic trends, causes of death